Fault detection of an industrial heat-exchanger - Dragan, Dejan (Strojniški vestnik, 2011)
One of the key issues in modelling for fault detection is how to accommodate the level of detail of the model description in order to suit the diagnostic requirements. The paper addresses a two-stage modelling concept to an industrial heat exchanger, which is located in a tyre factory. Modelling relies on combination of prior knowledge and recorded data. During the identification procedure, the estimates of continuous model parameters are calculated by the least squares method and the state variable filters (SVF). It is shown that the estimates are largely invariant of the bandwidth of the SVFs. This greatly reduces the overall modelling effort and makes the whole concept applicable even to less experienced users. The main issues of the modelling procedure are stressed. Based on the process model a simple detection system is derived. An excerpt of the results obtained on operating records is given.
Keywords: condition monitoring; fault detection; identification; identifikacija; industrial heat exchanger; industrijski prenosniki toplote; model-based detection; modeliranje; modelling; nadzor procesov; odkrivanje napak na osnovi modela; zaznavanje napak